Decelerated Early Growth in Infants of Overweight and Obese Mothers - Ode, Katie Larson (2012)
OBJECTIVE: To investigate the relationship between maternal pre-pregnancy BMI and early infant growth and body composition. STUDY DESIGN: Prospective cohort study performed at a University hospital/surrounding community. Ninety-seven non-diabetic mothers with singleton, term, healthy infants completed study visits at 2 weeks and 3 months of age. Pre-pregnancy, 59 mothers were normal weight, 18 were overweight, and 20 were obese. Infant anthropometrics and body composition via air-displacement plethysmography were measured. Infant feeding information and maternal pre-pregnancy weight were self-reported. Additional data were obtained via self-report and the medical record. Main outcome measures: change in weight, length, fat free mass, and fat mass from 2 weeks to 3 months of age. Analysis was by multivariate linear regression. RESULTS: At 2 weeks, anthropometrics and body composition did not differ across maternal BMI groups. At 3 months infants of overweight or obese mothers had gained less weight (p=0.02), grew less in length (p=0.01), and gained less fat mass (p=0.01). Adjustment for breastfeeding status and regression to the mean via conditional change variables did not alter the results. The results were not altered after adjusting for maternal glucose values from a 50 g glucose challenge and for maternal smoking in a subset including 80% of the women. CONCLUSIONS: Maternal overweight/obesity is associated with early deceleration in linear growth and adipose tissue accrual; replication of these findings is needed.